The Effectiveness of EXO-OLO TASK Learning Model in Improving Students’ English Ability at the Eighth Grade of SMPN 43 Padang - Yulia Novia Putri; Witri Oktavia (Journal of English Language Teaching, 2023)
This research is classified as a quasi-experimental research that is aimed to study whether or not the implementation of EXO-OLO TASK Learning Model does give a significant effect in improving students’ English ability. The study’s population was eighth-grade students at SMPN 43 in Padang. The population consists of 88 students who are classified into three classes. VIII 1 was selected as the experimental class while VIII 2 was selected as the control class through cluster random sampling method. This research was conducted over eight meetings and during school hours. In order to collect the data, the researcher used pre-test and post-test design. The pre-test and the post-test contained multiple choice questions. The result of the data analysis indicated that the null hypothesis (H0) examined in this study could not be accepted because the significant value of the two-tailed paired sample t-test was less than 0.05. The alternative hypothesis (HA), which indicated that the implementation of EXO-OLO TASK Learning Model does give a significant effect in improving students’ English ability, is accepted as the result of this study.